The decline of the artisans on Toronto City Council during the nineteenth century: 1834-1901 - DuWors, Richard (Ontario History)

(untitled) (The Ontario Historical Society, 2006)
In the mid-nineteenth century a major upheaval occurred in the work places of south-central Ontario. Craftsmen (artisans) were forced out of their small workshops into alienating factories, and lost control of their means of production. The contribution of this paper is to show a fall-off of participation by artisans on Toronto City Council at the same time. Data are presented from Toronto and similar cities to help explain the decline in participation by artisans. A model thought to apply widely by many historians is the “dispossession” of artisans from the means of production. This is often referred to as proletarianization. We add another important consequence: political dispossession.